Precios de productos almacenables: implicaciones del modelo de inventarios - Bobenrieth, Eugenio (Estudios de Economía, 2016)
Stock variations are recognized, by market participants and by the literature,as relevant in the determination of prices of storable assets. This paper presentsresults in the literature of rational expectations dynamic models based onstock variations, to explain price variations. The non-negativity restrictions inaggregate storage induce endogenous non-linearity in the market demand forthe asset. The model generates empirical regularities observed in price series:occasional sharp price increases, periods of stability, positive serial correlation,and conditional (and limit) asymmetry in the price distribution.